PERILAKU DAN ETIKA PEGAWAI NEGERI - Badrus Sholeh (Jurnal Manajemen Kepegawaian, 2008)
Indonesian State Officers – among them are Civil Servants- attempt to adapt from significant parts of the New Order’s government to independent groups professionally endorsed the bureaucracy for implementing government policy. However, the ethics of state officers managed by The Indonesian Laws no. 43/ 1999 is challenged by the rise of the spirit of democracy, regional autonomy, and human rights. Keywords : Civil servants, ethies and moral, professional